Ghost whisperer Season 2 Discs 1 & 2 - Hewitt, Jennifer Love, 1979-; Conrad, David, 1967-; Manheim, Camryn; Gray, John, 1958-; Paramount Pictures Corporation (Hollywood, Calif. : Paramount Pictures, 2007)
Melinda Gordon has the ability to communicate with the earthbound spirits of peple who have died, providing deeply moving and important closure for them and their loved ones. This season, Melinda and her husband, Jim Clancy are joined by new friend and employee Delia Banks, as Melinda battles a dark force taking over her beloved town of Grandview.
Disc 1: Love never dies ; Love still won't die ; Drowned lives ; The ghost within -- Disc 2: A grave matter ; The woman of his dreams ; A vicious cycle ; The night we met.
Episodes 1-8 of 22 originally broadcast on CBS television during the 2006-2007 season.
Special feature: Disc 1: Crystal ball mind game.
Created by John Gray.
Jennifer Love Hewitt, David Conrad, Camryn Manheim.
Not rated.
DVD, region 1, widescreen presentation; Dolby Digital 5.1 surround.
Keywords: Mediums -- Drama; Ghosts plays; Businesswomen -- Drama; Married people -- Drama; Drama; Ghost television programs; Television programs; Video recordings for the hearing impaired